Beauty pop. 6 - Arai, Kiyoko; Hubbard, Amanda; Nishida, Miho (San Francisco : VIZ Media, 2007)
The attempts by the Scissors Project to win the final match at the All-Japan Beauty Tournament are threatened by Narumi and Ochiai's rivalry over Kiri.
"Parental advisory Beauty pop is rated for T for Teen and is recommeded [sic] for ages 13 and up"--Colophon.
"This book reads from right to left".
Translated from the Japanese.
Adult.
Adult
Keywords: Beauty operators -- Comic books, strips, etc -- Fiction; Hairdressing -- Comic books, strips, etc -- Fiction; Interpersonal relations -- Comic books, strips, etc -- Fiction; Beauty operators -- Comic books, strips, etc -- Fiction; Comic books, strips, etc; Graphic novels; Hair -- Comic books, strips, etc -- Fiction; Interpersonal relations -- Comic books, strips, etc -- Fiction; Manga; Graphic novels